Dampak Penggunaan Aplikasi Paylater Terhadap Gaya Hidup Masyarakat - Alvida Dzattadini; Maya Anisa Nurpadilah; Riska Angraeni; Vyanara Aulyadisha; Radita Dian Eka Mauldya; Rama Wijaya Abdul Razak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to examine the impact of using the Paylater application on the lifestyle of people who are still not wise in using the paylater application. This research uses a quantitative approach method with the target population, namely the general public who use PayLater services or have used Paylater before. 114 respondents were selected using a questionnaire method using a Google form to conduct an online survey and collect data. The research results show that people rarely use paylater applications in daily use. Because paylater services have negative impacts, such as getting into debt if you use paylater excessively, then impulsive purchases due to easy access to paylater can encourage unplanned impulse purchases and other losses. And unwise use of paylaters can have a negative impact on people's lifestyles and people's finances. This research contributes to the understanding of the negative consequences of paylater for unwise users. This aims to help paylater service providers to increase education and financial literacy for their users, as well as encourage stricter regulations to minimize the potential for paylater abuse.